Three new species of Stactobiinae (Trichoptera: Hydroptilidae), new distributional records, and an updated checklist for Brazil - Cavalcante-Silva, Amanda; Santos, Allan Paulo Moreira; Calor, Adolfo Ricardo (Zootaxa, 2025)
Stactobiinae comprise 479 species worldwide. In Brazil, only 15 species have been reported, most of which are endemic to the Amazon rainforest and Atlantic Forest. In this work we provide the description and illustration of three new species from Brazil, two in the genus Flintiella and one in the genus Orinocotrichia. Flintiella angrisanoae sp. nov. differs from congeners by the inferior appendages being long and slightly sinuous and the phallic apex is divided into two asymmetrical lobes, with an ejaculatory duct protruding mesally. Flintiella quiteriae sp. nov. can be recognized by the phallic apex being deeply divided into two lobes, both curved to the right, with the left lobe overlapping the right. Orinocotrichia costae sp. nov. differs from congeners by truncated processes of segment IX and inferior appendages each with an anteroposterior membranous projection that narrows at the apex. We also are providing an updated checklist for Brazil, with new distribution records for seven Stactobiinae species: Bredinia espinosa Harris, Holzenthal & Flint 2002c; Flintiella andreae Angrisano 1995; F. astilla Harris, Flint & Holzenthal 2002b; F. boraceia Harris, Flint & Holzenthal 2002b; F. triaena Gama Neto, Ribeiro & Passos 2020, F. manauara Santos & Nessimian 2009, and F. pizotensis Harris, Flint & Holzenthal 2002b. Additionally, new illustrations and taxonomic comments are provided for F. triaena.